Parasitic isolation structure for mutual coupling reduction in a multiple input multiple output antenna - Godi, Revati C.; Patil, Rajendra R.; Kinagi, Revansiddappa S. (Institute of Advanced Engineering and Science, 2024)
This paper reports a design of 2×1 multiple input multiple output (MIMO) structure of antenna with 23×45 mm2 dimension. Each element in the MIMO antenna is a quarter wave transformer fed microstrip patch antenna. To lessen the effect of coupling, a rectangular parasitic decoupler is positioned between the two elements. Results report that antenna resonates at 6 GHz, coupling is reduced by 14 dB using parasitic decoupler S12 and S21 obtained with parasitic decoupler are same which -33.06 dB. The diversity gain (DG) is 9.99 dB, which is nearly close to 10 dB, and the envelope correlation coefficient (ECC) is less than 0.00034. These values reflect the good diversity performance. Measured findings match those from the simulation. As we confront the delicate environment, the proposed antenna is suited for number of wireless applications, including 802.11, 802.16 standards of IEEE.